High-Gain Phototransistors Based on a CVD MoS2 Monolayer - Zhang, Wenjing; Huang, Jing-Kai; Chen, Chang-Hsiao; Chang, Yung-Huang; Cheng, Yuh-Jen; Li, Lain-Jong (Advanced materials (Weinheim), 2013)
A phototransistor based on a chemical vapor deposited (CVD) MoS2 monolayer exhibits a high photoresponsivity (2200 A W−1) and an excellent photogain (5000). The presence of shallow traps contributes to the persistent photoconductivity. Ambient adsorbates act as p‐dopants to MoS2, decreasing the carrier mobility, photoresponsivity, and photogain.